Pentingnya Ide Pendidikan Athiyah Al-Abrasyi Bagi Sistem Pendidikan Islam Indonesia - Zaenullah; Farida Isroani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The culmination of the goal of Islamic education itself is to instill the value of life. So that Islamic education in this case becomes a value base not to forget the essence of human existence itself, namely, to be a human being who is safe in the afterlife. If there is an assumption that Islamic education is considered education that is lagging compared to education that developed from modern Western civilization, then this assumption is not based on a proportional argument. This is because the philosophy of Islamic education is that there is an integration of knowledge between religious knowledge and general science. The dichotomy of knowledge in Islam doesn't exist and shouldn't happen. The purpose of this article is to examine the thoughts of Muhammad Athiyah Al-Abrasyi who is known as an educational thinker who is critical of problems and phenomena in society. It is widely acknowledged that Atiyah is indeed an expert in her field by presenting an in-depth analysis of each of her thoughts. There are four basic principles in Muhammad Athiyah al-Abrasyi educational thinking, including First, equality in education, Second, academic freedom, Third, educational democracy, Fourth, educational equity.